Elastic and plastic deformations in a high entropy alloy investigated using a nanoindentation method. (January 2016) - Wu, D.; Jang, J.S.C.; Nieh, T.G.
Abstract: We employed instrumented indentation technique to study the elastic and plastic deformations in a face-centered cubic (fcc) high-entropy alloy NiFeCoCrMn. Single-crystal Ni was also examined for direct comparison. Tests were carried out using indenters with different tip radii to investigate the effect of indented volume on deformation processes. It was found that when the tip radius increased, the shear stress required for the occurrence of indentation pop-in decreased, which was attributable to a higher probability to find dislocations under a larger tip radius. We proposed a statistical model to describe the results quantitatively. In the plastic region, NiFeCoCrMn was much stronger than Ni, presumably resulted from a large lattice distortion in the multicomponent NiFeCoCrMn alloy. We found that the response of both materials at large indentation depth could be described by the classical Nix-Gao model, but when the indentation depth was shallow, the indenter tip must be treated as a sphere and Swadener's model offered a better description. In any event, it was necessary to introduce a scaling factor f to describe the effective stressed volume underneath the indenter tip to compensate for the overestimated hardness values. A map of indentation pressure against dislocation density was also summarized in this study. Graphical abstract: Highlights: The elastic/plastic behavior of NiFeCoCrMn are explored using nanoindentation. The pop-in stress in NiFeCoCrMn decreases with increasing the tip radius of the indenters. A statistical model is proposed to describe the cumulative probability of pop-in as a function of stress in NiFeCoCrMn. NiFeCoCrMn is stronger than single-crystal Ni due to the large lattice distortion in the multicomponent alloy. The indentation size effect in NiFeCoCrMn is observed and explained using the Nix-Gao model or the Swadener's model.